Диаграмма "pHсусп-состав" и ее свойства - Иконникова Л. Ф. Любовь Федоровна; Козик В. В. Владимир Васильевич; Минакова Т. С.; Борило Л. П.; Иконникова К. В. Ксения Владимировна (2001, 2001)
В фонде НТБ ТПУ отсутствует